Rsm Modeling and Optimization of Acid-Catalyzed Hydrolysis for Sustainable Bioethanol Production from Mixed Waste Biomass (International Journal of Environmental Sciences, 2025)
The generation of ethanol from the acid hydrolysis of Mixed Waste Biomass (MWB) was optimized through the use of response surface methodology (RSM) and central composite design (CCD). Responses were quantified regarding reducing sugars and biomass components, while independent variables included temperature, hydrolysis duration, and concentrations of sulfuric acid and sodium hydroxide. Under particular acid and basic conditions, the highest glucose concentrations were 0.563 ± 0.03 mg mL−1 and 0.486 ± 0.07 mg mL−1, respectively. A noteworthy 61% decrease in phenolic compounds was achieved through hydrolysate detoxification using 5% activated charcoal. For ten days, Saccharomyces cerevisiae fermented the detoxified hydrolysate. The ethanol yield peaked on day six of fermentation at 0.61 ± 0.03 g g−1. From S. cerevisiae, an ethanol concentration of 22.56% was obtained. These findings suggest that bioethanol is feasible. The ethanol yield peaked on day six of fermentation at 0.61 ± 0.03 g g−1. From S. cerevisiae, an ethanol concentration of 22.56% was obtained. These findings suggest that producing bioethanol from cellulosic waste commercially is feasible.